PENGARUH MEDIA BIGBOOK HIJAIYAH TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH ANAK USIA 4-5 TAHUN DI PUAD BAHAGIA BERSAMA KECAMATAN SIRAH PULAU PADANG OKI - Safitri, Nadia; Maryamah, Maryamah; Fahmi, Fahmi (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2025)
This study is entitled "The Influence of Big Book Media on the Ability to Recognize Hijaiyah Letters of Children Aged 4-5 Years at the Bahagia Bersama PAUD, Sirah Pulau Padang District, OKI Regency". This research method is an experiment "Pre-Experimental Design" using the One Group Pretest-Posttest design. The sample used was 20 children aged 4-5 years at the Bahagia Bersama PAUD, Sirah Pulau Padang District, OKI Regency. The results of this study used data collection techniques using observation, documentation and tests. The analysis technique uses normality test, homogeneity test, and hypothesis test. After conducting the initial test (pretest) and final test (posttest), the researcher then analyzed all the research results, from this study there is an influence of the big book hijaiyah media on the ability to recognize hijaiyah letters in early childhood, with t-count = 15.983 and t table = 2.101, because t-count> t-table (15.983 > 2.101). So it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that the big book hijaiyah media has an effect on the ability to recognize hijaiyah letters in children aged 4-5 years in the happy together